Analysis Of Effort Expectancy and Performance Expectancy on Intention to Use DANA Electronic Wallet (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research was aimed to determine the effect of effort expectancy and performance expectancy on intention to use DANA electronic wallet. The independent variables used were effort expectancy (X1) and performance expectancy (X2), while intention to use (Y) as the dependent variable. The research method used was descriptive and associative with quantitative approach. The population that used in this research was people of Sukabumi who know the DANA electronic wallet application with probability sampling as a sampling technique. Data was obtained by distributing questionnaires to around 400 respondents as a sample. The analytic technique used was multiple regression linier analysis by using SPSS 25 software. The result obtained was based on all the test that have been done in this research showed that effort expectancy and performance expectancy have a positive and significantly influenced the intention to use DANA electronic wallet application, and in this study performance expectancy was being the strongest variable affecting intention to use.
Keywords: Effort Expectancy; Performance Expectancy; Intention to Use